2012
DOI: 10.1038/ncb2444
|View full text |Cite
|
Sign up to set email alerts
|

Flippase-mediated phospholipid asymmetry promotes fast Cdc42 recycling in dynamic maintenance of cell polarity

Abstract: Lipid asymmetry at the plasma membrane is essential for such processes as cell polarity, cytokinesis and phagocytosis1-3. Here we identify the lipid flippase complex, composed of Lem3, Dnf1 or Dnf24, to play a role in the dynamic recycling of the Cdc42 GTPase, a key regulator of cell polarity5, in yeast. By using quantitative microscopy methods, we show that the flippase complex is required for fast dissociation of Cdc42 from the polar cortex by the guanine nucleotide dissociation inhibitor (GDI). A loss of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 42 publications
1
107
0
1
Order By: Relevance
“…A subsequent study obtained a better-constrained value for the abundance of Cdc42 (1 mM) [30], which we have adopted in the current model. In addition, we manually tuned some of the other parameters so that the model would reproduce three features extracted from imaging data: (i) the measured shape of the Cdc42 peak ( peak width at half height, 1.9 mm [31]); (ii) Cdc42 dynamics in the peak (FRAP recovery half-time, 3.5 s [32]) and our estimate of the amount of Cdc42 in the peak ( proportion of the total Cdc42, 4.6%).…”
Section: (I) Background On Model Developmentmentioning
confidence: 99%
“…A subsequent study obtained a better-constrained value for the abundance of Cdc42 (1 mM) [30], which we have adopted in the current model. In addition, we manually tuned some of the other parameters so that the model would reproduce three features extracted from imaging data: (i) the measured shape of the Cdc42 peak ( peak width at half height, 1.9 mm [31]); (ii) Cdc42 dynamics in the peak (FRAP recovery half-time, 3.5 s [32]) and our estimate of the amount of Cdc42 in the peak ( proportion of the total Cdc42, 4.6%).…”
Section: (I) Background On Model Developmentmentioning
confidence: 99%
“…Display rate, 1 frame /12 s. Related to Figure 5C. ; b (Berepiki et al 2011); c (Dagdas et al 2012); d (Chen and Thorner 2007); e (Semighini and Harris 2008); f (Jones and Bennett 2011); g ; h (Artiles et al 2009); i (Das et al 2013); j (Rank and Rayment 2013); k (Krappmann et al 2007); l (Pulver et al 2013); m (Park et al 1997); n (Brace et al 2011); o (Knaus et al 2007); p (Berepiki and Read 2013) (Glass and Lee 1992); g (Ferreira et al 1998); h (Hammond et al 2012); i (Li et al 2005); j (Park et al 2011) …”
Section: Figure S2mentioning
confidence: 99%
“…Functional studies revealed that flippases are involved in various vesicle transport pathways (5), and flippases in these functions are implicated in vesicle formation by inducing local membrane curvature (16,17). Flippases also regulate functions of membrane proteins by changing transbilayer phospholipid composition; changes in PE and PS content in the cytoplasmic leaflet of the plasma membrane regulate Cdc42p localization in polarized cell growth (18,19). However, other functions of flippases need to be investigated.…”
mentioning
confidence: 99%